DIFFICULTIES OF ANTHROPOLOGICAL EXPERT REPORT ON LAND CONFLICTS IN THE INDIGENOUS TERRITORY OF CABAGRA, COSTA RICA - Chaves Chang, Luis Diego (2025)
Cultural diversity is a sensitive issue in a monistic legal system that only recognizes the legally valid framework promulgated by state powers. Costa Rica has adopted anthropological expert reports to acknowledge the distinct legal notions held by indigenous peoples. However, these reports face two key challenges: first, courts often impose restrictive requests that prevent anthropologists from fully contextualizing cultural realities; second, internal diversity within communities creates competing notions of customary rights. The land conflicts in Cabagra exemplify how a single culture can generate divergent responses to the same issue, and how the official judicial system acts as a barrier to intercultural dialogue.